Improving Teachers' Scientific Skills Through Clinical Supervision: A Case Study at Aisyiyah Fastabiqul Khaerat Kindergarten - Ulfah, St. Maria (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
This study aimed to Enhance Teachers' Scientific Approach Skills Through Clinical Supervision. The study involved six Aisyiyah Fastabiqul Khaerat Kindergarten teachers in Majene District, West Sulawesi. The teachers underwent the clinical supervision process in two cycles. Five indicators of the scientific approach were assessed: observing, questioning, gathering information, associating, and communicating. The findings showed that clinical supervision significantly improved teachers' scientific approach skills (P<0.05) and showed consistent progress in each cycle. The coaching activities indicated that all teachers experienced significant improvements (P<0.05) in various aspects of their teaching performance. These supervision activities confirmed that coaching through clinical supervision provides substantial benefits, assisting kindergarten teachers in understanding their roles and functions, thus improving their professional competencies.